Pesantren dan Pendidikan Wanita Islam - Indria Nur (LPPM IAIN Sorong, 2015)
Islamic Boarding School (Pesantren) is considered by social society as agent of moral force that has given major contribution to the Islamic educational institutions in achieving what so called perfect human being, by upholding morals and morality in the society, particularly for women in Islam. Therefore, in order to create a generation of modern and intelligent Islamic BoardingnSchools that aims it education in advancing women’s Islamic education. How and in what way Ummul Mu’minin takes this role, has inspired researchers to study it. This paper is a case study that shows that the existence of women Islamic Boarding School (Pesantren) of Ummul Mukminin coordinated by ‘Aisyiyah in South Sulawesi region is one those Islamic education institusions that is able to accelerate Muslim women’s educational progress. Therefore this Pesantren is expected to continue enhancing its contribution in the community development, especially Muslim women, as well as the extensive development of Islamic thought that can answer the challenges of civilization in globalization era, even as a pioneer for orther Islamic educational institutions in shaping modern, intelligent, and Islamic women generations.